TATA KELOLA KEUANGAN DESA MELALUI SISTEM KEUANGAN DESA (SISKEUDES) DI DESA KEPENUHAN HILIR KECAMATAN KEPENUHAN KABUPATEN ROKAN HULU TAHUN 2017 - Ramadhani, Rizka; Wicaksono, Baskoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This research is motivated by the Kepenuhan Hilir Village which is determined as one of the best villages in terms of village financial management through the The village financial system Application from 10 selected villages in Rokan Hulu Regency. However, in its implementation there are still some obstacles that cause the disruption of the process of making administrative documents and reports in the Village of Fullness of Downstream so that it is feared that these achievements can slowly decline and be left behind by other villages that are more aggressive in solving the The village financial system application problem. So that the formulation of the problem in this study is, how the Village Financial Governance through the Village Financial System (The village financial system) in the Kepenuhan Hilir Village Kepenuhan Subdistrict Rokan Hulu District in 2017 and what are the factors inhibiting the Village Financial Governance through the Village Financial System (The village financial system) in the Kepenuhan Hilir Village In addition, this study aims to determine the Village Financial Management through the Village Financial System (The village financial system) in the Kepenuhan Hilir Village Kepenuhan Subdistrict Rokan Hulu District in 2017 and to find out the inhibiting factors of Village Financial Governance through the village financial system in Kepenuhan Hilir Village Kepenuhan Subdistrict Rokan Hulu District in 2017. The method used in this study was qualitative with a descriptive approach. The type of data in this study are primary data and secondary data. Data collection techniques in this study were interviews and documentation. The data analysis technique used is descriptive qualitative. The results of this study indicate that the Village Financial Governance through the Village Financial System (The village financial system) in the Kepenuhan Hilir Village Kepenuhan Subdistrict Rokan Hulu District in 2017 is carried out with five stages, namely: (1) Village Financial Planning Stage (2) Village Financial Implementation Stage (3) Village Financial Administration Stage (4) Village Financial Reporting Stage (5) Village Financial Accountability Stage. In addition, the Village of the Fullness of the Hilir in conducting village management also applies four principles, namely: the principle of transparent, accountable, participatory, orderly and budgetary discipline. While the Inhibiting Factors of Village Financial Governance through the Village Financial System. Keywords: Village Financial Governance, Village Finance